Criminal bankruptcy rules in Criminal Code of the Republic of Belarus in the context of bankruptcy law evolution - Zakhilko, Kiryl S. (Journal of the Belarusian State University. Law, 2019)
This article deals with tends of the criminal bankruptcy rules in Criminal Code of the Republic of Belarus in the context of bankruptcy law evolution. The main stages and the correlation of its development are analyzed. The reasons for the correlation are formulated. The weaknesses of art. 238–241 of the Criminal Code of the Republic of Belarus of 1999, identified as a result of their correlation with the main results and prospects for the development of the bankruptcy law in the Republic of Belarus are substantiated. On the basis the proposals for improving art. 238–241 of the Criminal Code of the Republic of Belarus are provided.